An enhanced method for registration of dental surfaces partially scanned by a 3D dental laser scanning. Issue 1 (January 2015) - Park, Seongjin; Kang, Ho Chul; Lee, Jeongjin; Shin, Juneseuk; Shin, Yeong Gil
Highlights A novel method is proposed for the accurate registration of partially scanned dental surfaces. The results showed that our method accurately registered partially scanned dental surfaces. Our method and its application are useful for orthodontic and prosthodontic treatment.